2022
DOI: 10.1186/s43055-022-00817-w
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced FLAIR versus contrast enhanced T1W images in evaluation of intraparenchymal brain lesions

Abstract: Background Patients with suspected brain lesions are usually evaluated by means of intravenous contrast materials. These lesions may demonstrate enhancement through different mechanisms. At most institutions, CE-T1WI is the preferred sequence. FLAIR is a sort of inversion recovery pulse sequence with a long TR, TE and T1 and hence effectually nulls signals from CSF. The long T1 causes mild T effect and this result in lesion enhancement on post-contrast study. Therefore, lesions demonstrating en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…This allowed us to detect disease activity and, as a result, provided a chance for better patient management. This was consistent with the findings of a prior study by EL Adalany et al [10], who discovered that CE-FLAIR images had more enhancing lesions than CE-T1WI images did, particularly in cases of multiple sclerosis (MS), where CE-FLAIR outperformed CE-T1WI in 90% of the cases. These findings were in good accord with another study [19] that evaluated CE-FLAIR against CE-T1WI, DWI, and ADC and found that CE-FLAIR was the most effective in active MS lesions due to its ability to attenuate the CSF signal and boost the detection of lesions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This allowed us to detect disease activity and, as a result, provided a chance for better patient management. This was consistent with the findings of a prior study by EL Adalany et al [10], who discovered that CE-FLAIR images had more enhancing lesions than CE-T1WI images did, particularly in cases of multiple sclerosis (MS), where CE-FLAIR outperformed CE-T1WI in 90% of the cases. These findings were in good accord with another study [19] that evaluated CE-FLAIR against CE-T1WI, DWI, and ADC and found that CE-FLAIR was the most effective in active MS lesions due to its ability to attenuate the CSF signal and boost the detection of lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we discovered that CEFLAIR allowed for better lesions definitions than CET1I in 54% and 46% of cases, respectively, with good agreement between their results (kappa 0.744). EL Adalany et al, reported in a prior study [10] that in 68.9% of the instances, CE-FLAIR pictures exhibited better lesion conspicuity than CE-T1WI, with good interobserver agreement found (Kappa = 0.848). In contrast to a study by Athar I, et al [17], which indicated a lower percentage (39.4%) of cases with better lesions conspicuity in CEFLAIR, our study and the study by EL Adalany et al The quantitative analysis of our cases revealed that the lesions' signal intensity (SI) was higher on CE-FLAIR images than it was on pre-contrast ones, confirming the existence of lesion enhancement on CE-FLAIR images.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations